Pelvic bone and hip joint hydatid disease revealing a retroperitoneal location - Abdelhalim El Ibrahimi; A. Ankouz; A. Daoudi; A. Elmrini (Orthopedic Reviews, 2009)
Echinococcosis is a parasitic disease produced by the larval stage of Echinococcus granulosus. Hydatid disease of bone is rarely seen in humans and it has been reported in only 1-2% of cases of echinococcosis. We present a patient who developed hydatid disease of the left pelvic and femoral bones with cartilage destruction of the ipsilateral hip joint revealing a retroperitoneal location of hydatid cyst. Hydatid bone must be present in the differential diagnosis of chronic monoarthritis; the risk is to perform a total hip replacement in a septic environment.